The Effect of Work Flexibility on the Performance of State Civil Apparatus Employees at the DKI Jakarta Provincial Education Office - Evitha Soraya; Supadi; Teguh Trianung Djoko Susanto; Shinta Doriza; Aeng Muhidin (Mimbar Ilmu, 2026)
This study aims to examine the influence of work flexibility on the performance of State Civil Apparatus (ASN) at the DKI Jakarta Provincial Education Office, focusing on four dimensions: time flexibility, timing flexibility, place flexibility, and cognitive flexibility. The study used a quantitative approach through a non-experimental survey of 111 respondents who were randomly selected from a population of 153 ASN. Data were collected through the Likert questionnaire and analyzed using simple linear regression. The results showed that work flexibility had a positive and significant effect on employee performance, with a regression coefficient value of 1.044 and an R² value of 0.673, which means that 67.3% of performance variations can be explained by work flexibility. Among the four indicators, timing flexibility contributed the most (27.2%) to performance improvement. The majority of employees are in the category of flexibility and moderate performance, which shows the potential for performance improvement if flexibility is increased to a high level. Based on these findings, it is suggested that the DKI Jakarta Education Office develop a results-based flexible work policy through a flexi-time system, a hybrid work environment, and time management and cognitive training. This approach is expected to form a more adaptive organization, encourage the retention of young employees, and improve the quality of an innovative and public service-oriented education bureaucracy.